ANALYSIS OF INFORMATION TECHNOLOGY INNOVATION GOVERNANCE USING COBIT: SYSTEMATIC LITERATURE REVIEW - Melinne Maldini Rosady; Alva Hendi Muhammad; Asro Nasiri (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Information Technology (IT) has become a critical element in all aspects of business, especially in the current digital era. To ensure continuity and operational effectiveness, companies must maintain their IT systems' security, availability and integrity. Success in managing IT innovation impacts operational efficiency and directly influences the company's overall performance and sustainability. Therefore, implementing effective IT innovation governance is crucial to reducing risks and maximizing benefits from IT investments. This research focuses on using the COBIT framework as the primary tool in managing IT innovation. COBIT, especially the COBIT 2019 version, is the dominant choice in innovation governance practices in the industrial and digital sectors. Through the Systematic Literature Review (SLR) method, this research identified and analyzed 30 related articles that provide in-depth insight into the application of COBIT in various industrial contexts. The research results highlight several challenges faced in implementing COBIT, including a need for a more in-depth understanding of this framework, a lack of proper documentation of work processes, and the need for clear operational standards to manage IT innovation effectively. Thus, this research not only provides practical guidance for practitioners in the field but also contributes a deeper understanding of the importance of integrated IT innovation governance with broader business strategy.